Ascorbate degradation in tomato leads to accumulation of oxalate, threonate and oxalyl threonate. (9th February 2017) - Truffault, Vincent; Fry, Stephen C.; Stevens, Rebecca G.; Gautier, Hélène
Summary: Ascorbate content in plants is controlled by its synthesis from carbohydrates, recycling of the oxidized forms and degradation. Of these pathways, ascorbate degradation is the least studied and represents a lack of knowledge that could impair improvement of ascorbate content in fruits and vegetables as degradation is non‐reversible and leads to a depletion of the ascorbate pool. The present study revealed the nature of degradation products using [ 14 C]ascorbate labelling in tomato, a model plant for fleshy fruits; oxalate and threonate are accumulated in leaves, as is oxalyl threonate. Carboxypentonates coming from diketogulonate degradation were detected in relatively insoluble (cell wall‐rich) leaf material. No [ 14 C]tartaric acid was found in tomato leaves. Ascorbate degradation was stimulated by darkness, and the degradation rate was evaluated at 63% of the ascorbate pool per day, a percentage that was constant and independent of the initial ascorbate or dehydroascorbic acid concentration over periods of 24 h or more. Furthermore, degradation could be partially affected by the ascorbate recycling pathway, as lines under‐expressing monodehydroascorbate reductase showed a slight decrease in degradation product accumulation. Significance statement: Ascorbate is a key molecule for plant metabolism and a marker of fruit nutritional quality, but how it is degraded is poorly studied in vivo . Here we used radiolabeling to determine which degradation products accumulate in tomato leaves, to evaluate how the ascorbate pool size affects the degradation rate, and to test whether the degradation rate could be reduced by manipulating an enzyme involved in ascorbate recycling. We suggest that controlling ascorbate degradation might be a means to increase or stabilize ascorbate content.